CRITICAL ANALYSIS OF HEALTH INSURANCE POLICIES IN EVALUATING COVERAGE, AFFORDABILITY, AND ACCESSIBILITY FOR DIVERSE POPULATIONS - Mohammed TurkiH AlHarth, Khalid Mohammed Abdu Madkhali, YahyaHadi Muhammad Al Mansour, Abdullah Hadi Muhammad Al Mansour, Saleh Yahia Ahmed Majrashi, Abdullah Hussain Mohammed Mahnashi, Abdullah RafanAwamAlmuhamidh, Saleh Amer Mohammed Al Harth, (Chelonian Research Foundation, 2022)
Health insurance policies are vital in facilitating healthcare access and affordability for different communities. This article aims to critically analyze other health insurance policy schemes, highlighting their optimality in meeting diverse demographic needs. Through the faithful undertaking of these metrics and using tables, charts, and graphs to determine what is being done well and at what areas should be brought attention to and made serviceable for now, that analysis shows the high levels of effectiveness of such individual approaches to health insurance policy that pay a lot of attention to equality and comprehensiveness. Policymakers can guarantee that health insurance products meet the needs of all population sections, irrespective of the differences in financial strength, educational level, and income, if the policies address disparities and enhance accessibility and affordability. As a result, health equity will receive support, and the healthcare system will become more inclusive. Keywords: health insurance, coverage’s, afford abilities, accessibility, and diversities, addressing equality.